‘Passive-active’ As a Functional Distinction in Husserl’s Theory of Consciousness - Maciejczak, Marek (Studia Philosophiae Christianae, 2022)
This article discusses passive and active aspects of consciousness as two equally justified roots of life experiencing the world (Weltbewusstseinsleben). The passive domain involves the synthesis of internal time, association, habituality, bodily aspects, etc. The active domain includes strictly cognitive competences of consciousness: thinking, judging, etc. What has been actively constituted becomes passive as the basic level for higher form of understanding. The two domains interweave, influence each other, complement each other, and also remain in a certain tension and discrepancy. In the broader perspective of the system of consciousness and its various layers, the passive-active differentiation must be treated functionally, and not as hierarchically arranged or constituted by separable concepts. It reflects the dynamics of the consciousness system at all its levels, and its meaning oscillates between the opposite and the overlapping. ——————— Received: 26/01/2022. Reviewed: 28/03/2022. Accepted: 12/05/2022.